Being a doctor : understanding medical practice - Wilson, Hamish (Hamish John); Cunningham, Wayne (Otago, 2013)
Sometimes caring for patients can leave clinicians feeling overwhelmed with the daily tasks of doctoring. As an antidote, this book explores principles and assumptions of modern medicine seldom taught in medical school. Starting with the meaning of suffering and how the "science" of medicine has evolved, the authors use many clinical stories to provide a fresh perspective on the work and roles of the modern doctor. Based on many years of teaching family physicians, the book argues that being a doctor is much more than simply knowing biomedical facts and having good clinical skills. It explores some of the major challenges facing physicians, including the doctor-patient relationship, the "heartsink" experience, and unwell patients for whom no disease can be found. The authors also introduce patient safety and self-care, two important issues for modern health professionals. For experienced doctors as well as for students and doctors in training, Being a Doctor moves beyond biomedicine, providing useful insights that explain how both doctors and patients think and behave. --Provided by publisher.